Optimization of the physical properties of magnetocaloric materials for solid state magnetic refrigeration. (25th April 2016) - Silva, D.J.; Bordalo, B.D.; Puga, J.; Pereira, A.M.; Ventura, J.; Oliveira, J.C.R.E.; Araújo, J.P.
Highlights: The influence of the physical properties on solid magnetic refrigerators is studied. An increase of density and heat capacity widens the temperature span. The operating frequency increases with the thermal conductivity. The adiabatic change of temperature has profound implications on the refrigerator. The maximization of the temperature span leads to smaller operating frequencies. Abstract: We have investigated numerically the dependence of the temperature span and optimum operating frequency of solid state magnetic refrigerators on the most important physical properties of magnetocaloric materials. We concluded that the temperature span depends inversely on the thermal conductivity of the magnetocaloric material and is proportional to the square root of its density, heat capacity and maximum adiabatic temperature variation upon the application/removal of a magnetic field ( Δ T a d m ). Also, and contrary to general belief, the increase of the thermal conductivity is not the only factor able to increase the optimum operating frequency. Reducing the density, heat capacity, Δ T a d m or broadening of the Δ T a d   ( T ) curve can result in larger operating frequencies. Our results show that a compromise between the maximum achievable temperature span and optimum operating frequency must be reached, as the increase of one reduces the other.